Atomic order and martensitic transformation entropy change in Ni–Co–Mn–In metamagnetic shape memory alloys. (1st January 2016) - Pérez-Sierra, A.M.; Bruno, N.M.; Pons, J.; Cesari, E.; Karaman, I.
Graphical abstract: Abstract: The martensitic transformation entropy changes, Δ S tr, measured from the stress-induced transformation in Ni–Co–Mn–In crystals with different degrees of long range L21 atomic order, follow a single temperature dependence and show good agreement with the theoretical Bragg–Williams approximation. The strong influence of the atomic order on Δ S tr is attributed to the large shift in the transformation temperatures caused by the change in atomic order and the natural temperature dependence of the austenite magnetization. The effects of associated changes in magnetic order have a negligible contribution to Δ S tr . Additional mechanical measurements performed under 1.6 T do not show any notable changes in Δ S tr .